The effect of duplex Surface mechanical attrition and nitriding treatment on corrosion resistance of stainless steel 316L - Li, Nana (Sci Rep, 2018)
Surface mechanical attrition treatment (SMAT) fabricates a nanostructured layer on the surface of 316L that possesses excellent mechanical properties. In this paper a duplex process combining SMAT with nitriding was performed, then the microstructure, hardness and corrosion properties of the treated materials were investigated by using X-ray diffraction (XRD), transmission electron microscopy (TEM), hardness tests, potentiodynamic polarization measurements, X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS). The results showed that this duplex surface treatment can effectively increase the hardness and corrosion resistance of the treated surface both at room temperature and in the simulated steam generator (SG) condition at high temperature and high pressure.